Pengaruh Celebrity Endorser Dan Kualitas Produk Terhadap Keputusan Pembelian Kosmetik Pixy - Tita Ajeng Novianti (PRAGMATIS, 2020)
This research aims to know the influence of Celebrity Endorser and the quality of the products Of Cosmetic Purchase PIXY in Surabaya. The independent variables consist of Celebrity Endorser and product quality while the dependent variable is the purchasing decision. In this research, the determination of the sampling done by the method of sampling procedure probably non purposive sampling total sample used was 39 people respondents. Methods of analysis used in this study was multiple linear regression. Test results showed the Fcount > Ftable which 28.690 >3.259446 of with a level of significance of 0.000 so that the celebrity endorser and the quality products have significant effects simultaneously against the purchasing of PIXY cosmetics in West Surabaya. T test results for variable celebrity endorser shows tcount < ttable which 1.918 < 2.028094 of with a level of significance of 0.063 so variable celebrity endorser had not significantly influence partially against purchasing decisions PIXY in Surabaya Western cosmetics. Then test results product quality variables show tcount > ttable which 5.590 > 2.028094 with significance level of 0.000 so that product quality variables have significant effects partially against the purchasing decision of PIXY cosmetics in West Surabaya. Based on testing of standardized coefficients beta the value of quality of products which 0.659 is greater than variable value celebrity endorser which 0.222 thus product quality variable is a variable which has a the dominant influence of purchasing decision of PIXY Cosmetics in West Surabaya.